Environmental Sustainability and Quality Education: Perspectives from a community living in a context of poverty - Overson Shumba; Raviro Kasembe; Cecilia Mukundu; Consolata Muzenda (Environmental Association of Southern Africa, 2008)
This paper presents perspectives on sustainability, quality and relevance of education found in a resettlement community in Zimbabwe. The exploratory research triangulated data from community meetings, interviews, focus group discussions and digital photography. The results showed that the community lived in a context of risk and vulnerability where a range of economic, cultural, social and environment issues and poor quality of education posed a threat to the quality of life. Tensions in the community and between the school and community, lack of solidarity, and the weakening of the traditional Unhu/Ubuntu moral and ethical framework contributed to the community's failure to envision and implement interventions towards quality education and towards sustainable development. The participatory research helped ease these tensions, enabling it to realise opportunities to deal with some of its sustainability issues. It enhanced teacher- community relations, leading to cooperation and solidarity around school improvement and environmental projects. The case study demonstrated the relevance of environmental education and education for sustainable development to quality of formal education in the school community and to the quality of formal and informal education in the broader community context.